2013
DOI: 10.1158/1078-0432.ccr-12-3167
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of HSP90 Inhibition for Neurofibromatosis Type 2

Abstract: Purpose The growth and survival of neurofibromatosis type 2 (NF2)–deficient cells are enhanced by the activation of multiple signaling pathways including ErbBs/IGF-1R/Met, PI3K/Akt, and Ras/Raf/Mek/Erk1/2. The chaperone protein HSP90 is essential for the stabilization of these signaling molecules. The aim of the study was to characterize the effect of HSP90 inhibition in various NF2-deficient models. Experimental Design We tested efficacy of the small-molecule NXD30001, which has been shown to be a potent HS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…Moreover, a significant decrease in HSP90AB1 phosphorylation was found not only in cultured cells but also in the xenograft phosphoproteome, indicating its crucial role in citreoviridin treatment. It has been reported that cells treated with HSP90 inhibitor showed reduced activity in signaling pathways, including Akt and MAPK/ERK cascades (63,64,67). Our study showed that the phosphorylation level of one key component involved in MAPK/ERK signaling, MAPK1, was markedly diminished at late stages in citreoviridin-stimulated responses.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, a significant decrease in HSP90AB1 phosphorylation was found not only in cultured cells but also in the xenograft phosphoproteome, indicating its crucial role in citreoviridin treatment. It has been reported that cells treated with HSP90 inhibitor showed reduced activity in signaling pathways, including Akt and MAPK/ERK cascades (63,64,67). Our study showed that the phosphorylation level of one key component involved in MAPK/ERK signaling, MAPK1, was markedly diminished at late stages in citreoviridin-stimulated responses.…”
Section: Discussionsupporting
confidence: 53%
“…In plasma, NXD30001 cleared quickly and reached near the lower limit of quantitation level at 6 h. In contrast, NXD30001 levels in brain, spinal cord, liver, and muscle were still above the neuroprotective concentration used in culture (40 nM, equivalent to 20 ng/g of tissue) at 6 h, despite substantial decrease from levels at 1 h. Drug levels in liver and muscle were much higher than those in nervous tissues. To convert ng/g to molar concentration, multiply by 0.5 turnover of cell signaling molecules that are HSP90 client proteins (Barluenga et al 2008Wang et al 2009;Zhu et al 2010;Tanaka et al 2013).…”
Section: G93amentioning
confidence: 99%
“…The antiproliferative activity of NXD30001 was tested in NF2-deficient cell lines and in human primary schwannoma and meningioma cultures in vitro, and in two allograft models and in one Nf2 transgenic model in vivo [Tanaka et al, 2013]. They found that NXD30001 induced degradation of client proteins and suppressed proliferation of NF2-deficient cells.…”
Section: Neurofibromatosismentioning
confidence: 99%